2013
DOI: 10.5032/jae.2013.04195
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Instruction and FFA/SAE Responsibilities Creating the Most Stress for Female Teachers in the Southeast

Abstract: Theory of Psychological Stress indicates that once a teacher appraises a stressor they will seek to master, tolerate, or reduce the demands of the stressor (Lazarus, 1991

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Given the perceived benefits of participating in CDEs as indicated by the research, it is no wonder that research in CDEs has also indicated a high degree of teacher stress and need for teacher professional development in CDE preparation. King et al, (2013) determined CDEs are one of the top five stressors for female agricultural educators in the southeast region of the United States. Further, experienced teachers spend more time on CDE preparation than first year teachers or student teachers and research indicates that providing time management workshops or professional development could help decrease teacher stress and increase preparation time (Torres et al, 2008).…”
mentioning
confidence: 99%
“…Given the perceived benefits of participating in CDEs as indicated by the research, it is no wonder that research in CDEs has also indicated a high degree of teacher stress and need for teacher professional development in CDE preparation. King et al, (2013) determined CDEs are one of the top five stressors for female agricultural educators in the southeast region of the United States. Further, experienced teachers spend more time on CDE preparation than first year teachers or student teachers and research indicates that providing time management workshops or professional development could help decrease teacher stress and increase preparation time (Torres et al, 2008).…”
mentioning
confidence: 99%
“…To emphasize the significance of CDEs, preparing students to participate in CDE competitions has been noted as a tenant of effective agriculture teachers (Roberts & Dyer, 2004). Due to the emphasis placed on CDEs, research indicates that CDE preparation is a stressor for female agricultural teachers in the southeastern region of the United States (King, Rucker, & Duncan, 2013). Additionally, teachers discuss a felt need for CDE-based professional development (Harris, 2008), and CDE professional development has been proposed to lessen teacher stress and increase preparedness (Torres et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The recognized disparity between teachers' value of SAE programs and their implementation of SAE programs suggests teachers may not be equipped to navigate the complexities of shaping a program to align with their standards, potentially leading to job dissatisfaction. Numerous studies have focused on agriculture teachers' roles related to job satisfaction (Cano & Miller, 1992;Grady & Burnett, 1985;King, Rucker, & Duncan, 2013;Torres et al, 2008); however, there is a gap in the literature regarding different generations of teachers' perceptions regarding ideal agriculture programs, as well as their abilities to shape their programs to meet those ideals.…”
Section: Introduction and Conceptual Frameworkmentioning
confidence: 99%